Growth and yield of carrot inoculated with Bacillus subtilis and Pseudomonas fluorescens - França, Ana Rosa da Silva; Borcioni, Elis; Paixão, Crysttian Arantes; Araújo, Ricardo Silva; Campos, Rangel Viganó de; Cruz, Sonia Purin da (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The objective of this study was to evaluate the effects of inoculation and co-inoculation with Bacillus subtilis and Pseudomonas fluorescens on carrots with reduced nitrogen use. A field experiment was carried on, with five treatments and five replicates, evaluating the growth and yield responses of inoculated carrots. Responses were observed in height only two weeks before harvesting, and the number of leaves was most affected from the beginning to the middle of the cultivation cycle. Although the fresh shoot mass was negatively affected by the inoculation treatments, the dry shoot mass did not respond to the rhizobacteria. The length of roots inoculated with P. fluorescens or co-inoculated with both bacteria increased from 21 cm, without inoculation, to 25 cm. The root volume and dry mass values were the same across the treatments. However, the fresh root mass was improved by between 70 and 81.8% with P. fluorescens and co-inoculation, respectively. More positive responses to inoculation were observed with reduced nitrogen levels, suggesting a potential in the rhizobacteria strains for use in reduced-input agricultural practices. Moreover, based on the findings, Pseudomonas fluorescens can be recommended as a plant growth-promoting microorganism in carrot cultivation.